Evaluasi Kerusakan Jalan Menggunakan Metode Pavement Condition Index (PCI) dan Surface Distress Iindex (SDI) Studi Kasus Jalan Pue Bongo – Kota Palu - E.R. Labaso; M.S. Ishak; M. Kasan (REKONSTRUKSI TADULAKO: Civil Engineering Journal on Research and Development, 2022)
Pue Bongo street is one of the urban roads where the pavement is damaged. Based on the observations made, there are many types of damage found, disturbance to road users and have a major impact on safety and comfort.The purpose of this research is to knowing the condition of the damage that occurred and the appropriate form of handling the problem of damage to the Pue Bongo street. Data collection was carried out along the Sta.0+000 to Sta.1+525 roads, namely visually. The data required are secondary data and primary data. Secondary data were obtained through the Department of Highways and Spatial Planning of Central Sulawesi Province. Primary data was obtained through a visual road condition survey using the PCI and SDI methods. The results of the analysis of the condition of the Pue Bongo pavement with an average PCI value of 37.90 indicate poor conditions, while the SDI average value is 76.56 with moderate conditions. The recomended treatment based on PCI method is reconstruction/recycling, for the SDI method the recomended treatment is maintenance. As for the handling of damage basd eon the MDP 2017, namely peeling and replacing the material in certain areas.